Abdominoinguinal approach in en bloc resection of retroperitoneal sarcoma involving iliac vessels with graft interposition - Lv, Ang; Liu, Bo-Nan; Liu, Dao-Ning; Wang, Zhen; Hao, Chun-Yi (Frontiers in Oncology, 2022)
Background: Retroperitoneal sarcomas (RPSs) located in the lower abdominal quadrants involving iliac vessels are difficult to manage. This study introduced a 5-step method for en bloc resection with graft interposition using the abdominoinguinal approach and evaluated its efficacy and safety. Methods: Data of 24 consecutive patients who met the inclusion criteria from 272 patients with RPS who underwent surgical treatment between April 2015 and April 2022 were retrospectively collected and analyzed. Results: The patients underwent left- or right-sided abdominoinguinal incision. In all patients, the abdominoinguinal approach provided good exposure, and complete resection was achieved. Iliac artery+vein, vein, and artery resection and replacement by graft were performed in 70.8%, 25.0%, and 4.2% of patients, respectively. Additional resected organs mainly included the colon, ureter, bladder, kidney, and abdominal wall. The median number of organs resected was 5. In 37.5% of patients, reconstruction of the lower abdominal wall and inguinal ligament was performed using a mesh. Venous graft thrombosis occurred in 21.7% of patients, while no patient had pulmonary embolism or arterial occlusion. Major complications occurred in 20.8% of patients, and no 30-day mortality was observed. The estimated 5-year local recurrence and distant metastasis rates were 54.4% and 22.1%, respectively, with a median recurrence-free survival of 27 months. Conclusions: En bloc resection of RPS involving iliac vessels with graft interposition using the abdominoinguinal approach is feasible and advantageous. Good complete resection rate and safety can be achieved. The long-term survival benefit of this surgical approach should be verified by further large-scale prospective controlled studies.